Apakah Spesialisasi Industri Auditor Berperan Dalam Pencegahan Kecurangan? - Insani, Yulia Sifa; sulhani, sulhani (Jurnal Riset Akuntansi dan Keuangan, 2020)
Abstract: This study aims to analyze the effect of auditor industry specialization in moderating the relationship between the characteristics of the audit committee and management against fraudulent financial statements. The populations in this study were non-financial companies listed on the Indonesia Stock Exchange in 2013-2015, with a sample of 284 companies and 833 observation data. The data in this study were analyzed using moderated regression analysis (MRA). The results of this study indicate that auditor industry specialization as a moderating variable can strengthen the negative influence between the characteristics of the audit committee (tenure) and management (gender) againts fraudulent financial statements. But auditor industry specialization reinforces the positive influence between the characteristics of the audit committee's financial expertise on fraudulent financial statements. The practical implication for companies is that companies should choose specialist auditors to ensure that the financial statements presented are free from fraud. In addition to the users of financial statements, the use of specialist auditors can help initial identification of the quality of information conveyed in the company's financial statements. Future research is expected to use other proxies to determine the characteristics of audit committees such as the independence of the audit committee and the level conflict of interest between management and company.Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh spesialisasi industri auditor dalam memoderasi hubungan antara karakteristik komite audit dan manajemen terhadap kecurangan laporan keuangan. Populasi dalam penelitian ini adalahÂ  perusahaan non keuangan yang terdaftar di Bursa Efek Indonesia pada tahun 2013-2015, dengan sampel 284 perusahaan dan 833 data observasi. Data dalam penelitian ini dianalisis dengan menggunakan moderated regression analysis (MRA). Hasil penelitian ini menunjukkan bahwa spesialisasi industri auditor sebagai variabel moderasi dapat memperkuat pengaruh negatif antara karakteristik komite audit (masa jabatan)Â  dan manajemen (gender) kecurangan laporan keuangan. Namun spesialisasi industri auditor memperkuat pengaruh positif antara karakteristik keahlian keuangan komite audit terhadap kecurangan laporan keuangan. Implikasi praktis bagi perusahaan adalah perusahaan sebaiknya memilih auditor spesialis untuk memastikan bahwa laporan keuangan yang disajikan bebas dari kecurangan. Selain itu bagi pengguna laporan keuangan, penggunaan auditor spesialis dapat membantu identifikasi awal mengenai kualitas informasi yang disampaikan dalam laporan keuangan perusahaan. Penelitian di masa depan diharapkan untuk menggunakan proksi lain untuk mengetahui karakteristik komite audit seperti independensi komite audit dan besarnya konflik kepentingan manajemen dengan perusahaan.